PEMANFAATAN EKSTRAK DAUN TEMBAKAU (Nicotiana tabacum L) UNTUK MENGENDALIKAN ULAT GRAYAK (Spodoptera litura F) PADA TANAMAN SAWI (Brassica juncea L.) DI LAPANG - Maria Goreti Firma (AGRICA, 2019)
This study aims to determine the effect of tobacco plant extracts on mortality of armyworm pests (Spodoptera litura F.) and determine the optimum concentration of tobacco leaf extracts on mortality of armyworm caterpillars on mustard plants in the field. The design used in this study was a Randomized Block Design (RBD) consisting of 5 treatments and 4 replications namely T1: 175 ml/L concentration of tobacco leaf extract, T2: 350 ml/L concentration of tobacco leaf extract T3: Concentration of 525 ml/L tobacco leaf extract, T4: Concentration of 700 ml/L tobacco leaf extract, T5: Concentration of 875 ml/L of tobacco leaf extract. The observation variables in this study were pest mortality (%), damage intensity (%), plant fresh weight, and fresh weight per hectare (ton). The results showed that the concentration of tobacco leaf extracts significantly affected the mortality of Spodoptera litura F. At the concentration of T5 treatment (875 ml) were the lowest damage, pest mortality, fresh weight of the mustard plant, and fresh weight per hectare of was 9.75%, 88%, 109.25 gr, and27.31 tons respectively.